Characterization of the honeybee venom proteins C1q-like protein and PVF1 and their allergenic potential. (August 2018) - Russkamp, Dennis; Van Vaerenbergh, Matthias; Etzold, Stefanie; Eberlein, Bernadette; Darsow, Ulf; Schiener, Maximilian; De Smet, Lina; Absmaier, Magdalena; Biedermann, Tilo; Spillner, Edzard; Ollert, Markus; Jakob, Thilo; et al.
Abstract: Honeybee ( Apis mellifera ) venom (HBV) represents an ideal model to study the role of particular venom components in allergic reactions in sensitized individuals as well as in the eusociality of Hymenoptera species. The aim of this study was to further characterize the HBV components C1q-like protein (C1q) and PDGF/VEGF-like factor 1 (PVF1). C1q and PVF1 were produced as recombinant proteins in insect cells. Their allergenic properties were examined by determining the level of specific IgE antibodies in the sera of HBV-allergic patients (n = 26) as well as by their capacity to activate patients' basophils (n = 11). Moreover, the transcript heterogeneity of PVF1 was analyzed. It could be demonstrated that at least three PVF1 variants are present in the venom gland, which all result from alternative splicing of one transcript. Additionally, recombinant C1q and PVF1 from Spodoptera frugiperda insect cells exhibited specific IgE reactivity with approximately 38.5% of sera of HBV-allergic patients. Interestingly, both proteins were unable to activate basophils of the patients, questioning their role in the context of clinically relevant sensitization. Recombinant C1q and PVF1 can build the basis for a deeper understanding of the molecular mechanisms of Hymenoptera venoms. Moreover, the conflicting results between IgE sensitization and lack of basophil activation, might in the future contribute to the identification of factors that determine the allergenic potential of proteins. Highlights: C1q-like protein and PVF1 are honeybee venom components that induce sIgE in honeybee-venom allergic patients. At least three PVF1 variants are present in the venom gland, resulting from alternative splicing of one transcript. Both proteins are unable to activate basophils, questioning their clinical relevance. The recombinant proteins can contribute to a deeper understanding of the molecular mechanisms of Hymenoptera venoms.